2016
DOI: 10.1177/0033294116662842
|View full text |Cite
|
Sign up to set email alerts
|

Adult Playfulness, Humor Styles, and Subjective Happiness

Abstract: Playfulness has been referred to as a disposition that involves reframing a situation to amuse others and to make the situation more stimulating and enjoyable. It may serve to shift one's perspective when dealing with environmental threats. Despite all the benefits of playfulness towards psychological well-being, it remains a largely understudied subject in psychology, particularly in Chinese societies. Hence, this study examined the association between adult playfulness, humor styles, and subjective happiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 38 publications
3
44
0
6
Order By: Relevance
“…Similar pattern have been reported in previous studies, such that adaptive humor styles were mostly found to be related to measure of well-being as compared to maladaptive humor styles [19,23]. As mentioned earlier, these two humor styles occur solely within the social situations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar pattern have been reported in previous studies, such that adaptive humor styles were mostly found to be related to measure of well-being as compared to maladaptive humor styles [19,23]. As mentioned earlier, these two humor styles occur solely within the social situations.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies show that use of affiliative and self-enhancing humor would lead to lower depression and anxiety, higher positive affect, and higher self-esteem; whereas use of selfdefeating humor would lead to increased depression and anxiety, greater negative affect, and lower self-esteem [19][20][21][22][23]. Besides, self-enhancing humor was found to be positively associated with the ability to manage emotions whereas the ability to perceive emotions accurately was negatively related to aggressive and self-defeating humor [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, valuation of humor was positively correlated with adaptive humor and self-esteem. This implies that the more students valued humor, the more adaptive humor styles they used, and the better they felt about themselves [25,26]. This also reflects an important factor in determining who we are and how we think of ourselves [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…Further, research on adult playfulness is just beginning to be con-ducted in nonWestern societies (cf. Barnett, 2017;Pang & Proyer, 2018;Yue, Leung, & Hiranandani, 2016), an especially significant direction in that fundamental belief systems and negative attitudes towards play prevail in many cultures (cf. Bai, 2005;Holmes, 2001).…”
Section: Limitationsmentioning
confidence: 99%